HOA DAM SINH TINH DECOCTION AND ITS PROTECTIVE EFFECTS ON TESTICULAR FUNCTION IN EXPERIMENTAL STUDY (Vietnam Journal of Community Medicine, 2026)
Objectives: To evaluate the protective effects of the herbal formula Hoa dam sinh tinh decoction on testicular function in an experimental model.Subject and methods: Hoa dam sinh tinh decoction was evaluated in a controlled experimental study on adult male white rats. 40 adult male white rats were randomly divided into 4 groups. The rats were administered sodium valproate to induce testicular dysfunction, concurrently with the herbal formula for 7 weeks to evaluate its protective effects. The evaluated parameters included serum testosterone levels, testicular and epididymal weights, sperm density, motility, and viability, as well as histological structures.Results: Serum testosterone levels in the model group decreased significantly compared with the biological control group (4.20 ± 1.28 nmol/L vs. 9.02 ± 2.24 nmol/L; p < 0.01). Groups receiving Hoa dam sinh tinh decoction concomitantly with sodium valproate demonstrated protective effects on testicular function, as evidenced by improved testosterone levels (especially in the high-dose group: 10.02 ± 1.03 nmol/L), increased testicular and epididymal weights, and improved sperm density, viability, and motility compared with the model group. In the high-dose group, sperm density reached 101.90 ± 12.68 × 106/mL and sperm viability reached 85.90 ± 6.05%. Sperm morphology and testicular histopathological structure were also better preserved compared with the model group.Conclusion: The herbal formula Hoa dam sinh tinh decoction at doses of 15 g/kg/day and 45 g/kg/day demonstrates protective effects on testicular function in male rats treated with sodium valproate, as evidenced by its ability to attenuate adverse effects on testosterone levels, testicular and epididymal weights, sperm parameters, and testicular histopathological structure.
Keywords: Hoa dam sinh tinh decoction, sperm, testosterone, testicular histopathological structure.